The Mediator subunit MED1/TRAP220 is required for optimal glucocorticoid receptor-mediated transcription activation - Chen, Wei (Oxford University Press, 2007)
The MED1/TRAP220 subunit of the Mediator plays a key role in facilitating ligand-dependent interactions of this multisubunit coactivator complex with nuclear receptors through their ligand binding domains. The isolated MED1/TRAP220 protein previously was shown to interact with glucocorticoid receptor (GR) in a ligand-dependent manner. However, the functional role of MED1/TRAP220, within the context of the entire Mediator, is not well studied in GR-mediated transcription. In this study, we show that GR binds directly to the Mediator complex and that both LXXLL motifs of MED1/TRAP220 contribute to its binding to GR. Furthermore, using a Med1/Trap220(−/−) mouse embryonic fibroblast (MEF) line that lacks entirely MED1/TRAP220, we show that MED1/TRAP220 enhances GR-mediated transcription from an MMTV promoter based-reporter gene and that mutations in the MED1/TRAP220 LXXLL motifs reduce, but do not eliminate, GR-dependent transcription. An analysis of endogenous genes in Med1/Trap220(−/−) cells has confirmed a variable MED1/TRAP220 requirement for different GR target genes. Taken together, these findings support the idea that Mediator, at least in part through MED1/TRAP220, plays a coregulatory role in ligand-dependent GR-mediated gene expression.